Creating New Forest Governance Structure for the 12.7 Million-Promise - Ahmad Maryudi (Jurnal Ilmu Kehutanan, 2017)
In the National Mid-Term Development Plan for2014-2019, the Government of Indonesia has an ambitious plan to allocate 12.7 million ha of state forests for local communities and indigenous peoples through social forestry projects. Recently, President Joko Widodo has taken a strong step toward fulfilling the promise by handing of 13,000 ha to nine customary communities. He underlined that it is a beginning of the big thing. The policy is a strong political will; it is the first time that customary land rights are legally recognized. Over the years, uses of forest resources by local people were prevented (Maryudi 2011; Maryudi &Krott 2012a). Webb (2008: 26) argues that in many economically-developing countries, traditional forest uses are often labelled as illegal since the governments favour corporate-based/ industries forestry as development strategies. The policy breakthrough is a result of long struggles to main streaming social forestry, nearly 50 years after Jack Westoby’s anthropocentric views regarding forestry and forest management. Before his death, Westoby stated: “a clear forest policy is one condition of a truly social forestry...all forestry should be social”. His thinking seemed to repudiate the idea of forest-based industrial development (Leslie 1989). As he claimed, the enormous expansion in the utilisation of the tropical forests had limitedly done for the people that continued to live in chronic poverty. At the same time, the application of the industrial forestry in the developing world led to environmental crisis of rapid forest destruction (Westoby 1969). Westoby’s address to the 1978’s World Forestry Congress further inspired forest policy makers across the globe, including in Indonesia, to formulate strategies that can tackle both problem in one single package of forest problem (Maryudi et al. 2012). We have since witnessed experiments and pilot projects translating the alternative thinking on the ground,also as manifestation of decentralization anddevolution policy (Sahide et al. 2016a). In Indonesia,however, social forestry is often understood as only involvement of local people in forest management that generate subsistent livehood (Maryudi & Krott2012b). Numerous pilot projects and programs failed to address the central issue of power relations and decision-making authority (Maryudi 2014; Sahide etal. 2016b). In most cases, external actors remain powerful in shaping the programs; they try to skew the outcomes of decision-making processes in their direction (Schusser et al. 2015; Schusser et al. 2016;Mery et al. 2010). Local communities, who are supposedly the core actors, remain peripheral; social forestry has yet to produce the intended outcomes as a result.What does that mean in relation to the new promise by the Indonesian government to rural communities? Rights and access are two central keywords for social forestry. There might be arguments that in social forestry programs in Indonesia, local people have been granted with different types of rights so that they can benefit from the forest resources. Such is not always the case. Quite often, local communities are not able to benefit from the forests despite being given the rights (see Maryudi2014). As such, conflicts persist even in forests where social forestry is implemented (see Maryudi et al.2015). Ribot and Peluso (2003) distinguish access from property. To them, access is defined as “a bundle ofpower” whereas property is defined as “a bundle ofrights”.The new policy clearly needs new approach so that we do not repeat the same mistakes and consequences. New forest governance structure is needed. Local communities should have explicit mandate and legal authority(Krogman & Beckley2002) and power “to influence decisions regarding management of forests, including the rules of access and the disposition of products” (McDermott &Schrekenberg 2009:158). Thus, genuine social forestry entails the following characteristics (Charnley & Poe2007: 1) the degree of responsibility and authority for forest management is formally vested by the state to the local communities, 2) a central objective of forest management is to provide local communities with social and economic benefits from the forest, and 3)ecollogically sustainable forest use is a central management goal, with forest communities taking some responsibility for maintaining and restoring forest health.